Oxidative Stress and Drugs of Abuse: An Update - Cunha-Oliveira, Teresa; Cristina Rego, Ana; R. Oliveira, Catarina (Mini-Reviews in Organic Chemistry, 2013)
Drug addiction is a public health and social burden. Presently, the most abused illicit substance is cannabis, followed by amphetamines, cocaine and opioids, with different prevalence in different countries. Several evidences support a role for oxidative stress in the toxicity induced by many drugs of abuse in different organs, such as the brain, heart, liver or kidneys. This leads to oxidation of important cellular macromolecules, and may culminate in cell dysfunction and death. In this review we describe the evidences for oxidative damage and depletion of antioxidants upon exposure to drugs of abuse, especially amphetamines, cocaine and opiates. We also discuss the sources of oxidative stress induced by drugs of abuse, including oxidative metabolism of drugs, oxidative metabolism of monoamines by monoamine oxidases or by auto-oxidation, mitochondrial dysfunction, excitotoxicity, microglial activation, inflammation, hyperthermia and the effects of drug interactions. These consolidate oxidative stress as a relevant mechanism contributing for the cytotoxicity of drugs of abuse and for behavioral changes associated with drug addiction.
Keywords: oxidative stress